TAXOL (ANTICANCER DRUG) PRODUCING ENDOPHYTIC FUNGI: AN OVERVIEW - SONAIMUTHU VISALAKCHI; JOHNPAUL MUTHUMARY (International Journal of Pharma and Bio Sciences, 2010)
In this review, we mainly focused on characterization of the taxol producing endophytic fungi from medicinal plants. The different endophytic fungi were isolated and characterized for its potential in taxol production in past two decades. All the strains were identified based on the morphology of the fungal culture and the characteristics of the spores and with specific molecular techniques. The endophytic strains were grown in MID liquid medium for the taxol production. The qualitative and quantitative measures were analyzed to confirm the presence of taxol. The amounts of taxol production were quantified by high performance liquid chromatography which suggests that the fungus can serve as a potential material for genetic engineering to improve the taxol production. Further, the endophytic fungal taxol have strong cytotoxic activity on different human cancer cells in vitro, tested by apoptotic assay